Processing method of AG (anti-glare) glass

By sandblasting, laser engraving, chemical etching and multi-step processing of AG anti-glare glass, the problems of low accuracy and efficiency in AG glass processing are solved, and efficient and accurate edge and hole chamfering processing is achieved, reducing cost and damage rate.

CN119609948AActive Publication Date: 2025-03-14BIEL OPTIC HUIZHOU +1

Patent Information

Application Number
CN202510048074.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-14
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

It is difficult to achieve high-precision and efficient edge chamfering and hole chamfering processing during the processing of AG anti-glare glass, and existing methods are prone to cracks, edge collapses and high processing costs.

Method used

After sandblasting large-scale glass incoming materials, the glass sheet is chamfered and pretreated by laser engraving, then chemically etched in the etching liquid, and finally the outer shape and hole lobes are used to achieve efficient and accurate processing.

Benefits of technology

It improves the processing accuracy and efficiency of AG glass, reduces product damage rate and processing cost, and reduces the requirements for operator skills.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609948A_ABST
    Figure CN119609948A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of glass processing, and discloses a processing method of AG (anti-glare) glass, which is high in processing precision and efficiency, low in product breakage rate and processing cost and low in skill requirements on operators, and comprises the following steps: S1, carrying out sand blasting on a glass incoming material, so that a sand surface is formed on the front surface of the glass, and a non-sand surface is formed on the back surface of the glass; s2, cutting the sand-blasted glass to form a plurality of glass sheets; s3, a laser beam is emitted from the non-sand surface of the glass sheet, so that a chamfering pretreatment area, a hole pretreatment area and a hole chamfering pretreatment area are formed in the glass sheet through laser internal carving; s4, putting the glass sheet into an etching solution for chemical etching; s5, carrying out appearance splitting on the glass sheet so as to form a chamfer on the edge of the glass sheet; and S6, carrying out hole splitting on the glass sheet by adopting ultrasonic wave under-liquid splitting, so that hole sites are formed in the hole pretreatment area and the hole chamfering pretreatment area on the glass sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass processing, and in particular to a processing method of AG anti-glare glass. Background Art

[0002] AG anti-glare glass is a glass that has been treated by chemical process to change the original reflective surface of the glass into a matte diffuse reflective surface. It can reduce the interference of ambient light, has excellent anti-reflection performance and light transmittance, and is widely used in display devices, touch screens, optical components and other fields. In the processing of AG glass, especially in the chamfering and drilling links, due to the hardness and brittleness of the material itself, the processing of AG glass is difficult, and it is easy to produce cracks, edge collapse and other problems, affecting the aesthetics and performance of the product. At present, the edge chamfering of AG glass mainly adopts three methods: laser chamfering, mechanical chamfering and sandblasting chamfering. Among them, laser chamfering uses laser to precisely heat and melt the edge of AG glass, and then controls the laser moving path and speed to achieve efficient and precise processing of edge chamfering. It is not easy to produce cracks and edge collapse, but the laser equipment is expensive and complicated to operate, which will increase the processing cost of glass. Mechanical chamfering uses mechanical cutting tools, such as grinding heads or milling cutters, to cut and chamfer the edges of AG glass. It has high processing accuracy and can be applied to AG glass of various sizes and shapes. However, this method requires precise control of cutting parameters and paths to ensure the quality and accuracy of chamfering, and requires high skills of operators. Sandblasting chamfering uses high-speed moving sand particles to impact and cut the edges of AG glass to form the desired chamfer shape. It has low processing cost, is easy to operate, and is suitable for mass processing. However, this method requires control of sandblasting parameters and paths, and the chamfering accuracy is not as good as laser and mechanical chamfering. It is easy to produce tiny defects, which in turn cause glass damage.

[0003] The hole chamfering of AG glass mainly adopts three methods: mechanical drilling and chamfering, integrated laser drilling and chamfering, and sandblasting hole chamfering. Among them, mechanical drilling and chamfering first uses mechanical drilling equipment to drill the required holes on the AG glass, and then uses the chamfering tool to chamfer the edges of the holes. This method is suitable for chamfering holes with larger apertures and thicker glass, and has higher processing accuracy. However, it requires two processing steps, has low processing efficiency, and may increase the risk of cracks and edge collapse. Laser drilling and chamfering integration uses a laser beam to perform thermal processing on the glass, causing the glass to partially melt, evaporate or vaporize, thereby forming a straight-through hole, and then uses a laser beam to heat the hole mouth after drilling, causing the glass to partially melt and flow, thereby forming a chamfer; this method is efficient and accurate, and drilling and chamfering can be completed in one processing, which can reduce the risk of cracks and edge collapse. However, the equipment used for its processing is expensive, the operation is complicated, and the operator's skills are required to be high. Sandblasting hole chamfering uses high-speed moving sand particles to impact and cut the edge of the hole to form the desired chamfer shape. It is low-cost and easy to operate, and is suitable for occasions where the chamfering accuracy is not high. However, its chamfering accuracy is low, it is easy to produce tiny defects, and it may affect the accuracy and size of the hole. Summary of the invention

[0004] Based on this, it is necessary to provide a processing method for AG anti-glare glass with high processing accuracy and efficiency, low product breakage rate and processing cost, and low skill requirements for operators in order to address the above-mentioned shortcomings.

[0005] A method for processing AG anti-glare glass comprises the following steps:

[0006] S1. Sandblasting the incoming glass material so that the front side of the glass forms a sand surface and the back side of the glass forms a non-sand surface;

[0007] S2, cutting the sandblasted glass to form a number of glass sheets;

[0008] S3, irradiating a laser beam from the non-grinded surface of the glass sheet, so that the inside of the glass sheet is laser engraved to form a chamfer pre-processing area, a hole pre-processing area and a hole chamfer pre-processing area;

[0009] S4, placing the glass sheet into an etching solution for chemical etching;

[0010] S5, performing external cracking on the glass sheet so that the edge of the glass sheet is chamfered;

[0011] S6. Using ultrasonic underwater cracking to crack the glass sheet, so that holes are formed in the hole pretreatment area and the hole chamfer pretreatment area on the glass sheet.

[0012] In one embodiment, in step S1, the sandblasting pressure of the glass material is 0.1-0.7 MPa, the sand particle size is 0.2-0.5 mm, the sandblasting speed is 20-30 m / s, the sandblasting angle is 45°-90°, the sandblasting distance is 10-30 cm, and the roughness of the glass sand surface is Ra 0.5-1.0 μm.

[0013] In one embodiment, step S2 comprises:

[0014] S21. Apply protective oil or cover the sand surface of the glass with a protective film;

[0015] S22, cutting the glass into a plurality of glass sheets.

[0016] In one embodiment, in step S21, the viscosity of the protective oil is 20-50 cps.

[0017] In one embodiment, in step S22, a cutter wheel or a laser is used to cut the glass.

[0018] In one embodiment, in step S3, the laser beam power is 50-100 W, the frequency is 50 KHZ-250 Hz, and the chamfering speed is 5-100 mm / s.

[0019] In one embodiment, before step S4, the protective oil or protective film on the surface of the glass sheet is removed.

[0020] In one embodiment, in step S4, the glass sheet is placed in a concentrated solution of NaOH or KOH with a mass fraction greater than 50% and a temperature greater than 120° C. for chemical etching.

[0021] In one embodiment, in step S5, CO2 laser cracking, liquid nitrogen cracking, or ice water quenching cracking is used to crack the glass sheet.

[0022] In one embodiment, in step S6, the glass sheet is placed in a citric acid solution with a concentration of 1%-30% or a NaOH solution with a concentration of 1%-20% to perform ultrasonic underwater cracking.

[0023] The processing method of the AG anti-glare glass of the present invention has at least the following beneficial effects:

[0024] 1) Pre-process the glass sheet with laser engraving. By shaping the laser beam, the position of the laser engraving can be accurately controlled to achieve efficient and precise processing of AG glass, thereby improving processing accuracy and yield rate;

[0025] 2) The laser beam is incident from the non-grit surface of the glass sheet, which reduces the damage area of ​​AG glass, reduces cracks and edge collapse during processing, and reduces the breakage rate;

[0026] 3) Combine sandblasting of large pieces of glass with laser processing to batch etch and crack glass sheets, thus achieving fast and efficient processing of AG glass and improving production efficiency;

[0027] 4) By optimizing the processing flow, waste and loss in the processing process are reduced, and the processing cost is reduced. It has low skill requirements for operators and reduces the difficulty of product processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of a method for processing AG anti-glare glass in one embodiment of the present invention;

[0029] Figure 2 A schematic diagram of AG anti-glare glass during sandblasting in one embodiment of the present invention;

[0030] Figure 3 It is a schematic diagram of AG anti-glare glass when coated with protective oil in one embodiment of the present invention;

[0031] Figure 4 A schematic diagram of AG anti-glare glass during laser inner engraving in one embodiment of the present invention;

[0032] Figure 5 This is a comparison diagram of the effects of a glass sheet when a laser beam is incident from a non-grinded surface and from a grained surface in one embodiment of the present invention;

[0033] Figure 6 This is a comparison diagram of the effects of normal chamfers and abnormal chamfers processed by AG anti-glare glass in one embodiment of the present invention;

[0034] Figure 7 A schematic diagram of laser engraving in one embodiment of the present invention;

[0035] Figure 8 This is a comparison diagram of the effects of the edge chamfer of the AG anti-glare glass before and after liquid polishing in one embodiment of the present invention;

[0036] Fig. 9 This is a comparison diagram of the effects of the hole and hole chamfer of the AG anti-glare glass before and after liquid polishing in one embodiment of the present invention;

[0037] Fig.10 This is a comparison diagram of the effects of the sanded surface and the non-sanded surface of the AG anti-glare glass after liquid polishing in one embodiment of the present invention;

[0038] Fig.11 A schematic diagram of AG anti-glare glass being cracked under ultrasonic liquid in one embodiment of the present invention;

[0039] Fig.12This is a comparison diagram of the effects of AG anti-glare glass before and after the hole crack in one embodiment of the present invention;

[0040] Fig.13 The effect of the chamfer of the front edge of the AG anti-glare glass in ultrasonic liquid cracking in one embodiment of the present invention Figure 1 ;

[0041] Fig.14 The effect of the chamfer of the front edge of the AG anti-glare glass in ultrasonic liquid cracking in one embodiment of the present invention Figure 2 ;

[0042] Fig.15 The effect of the AG anti-glare glass on the chamfer of the front hole of the crack under ultrasonic liquid in one embodiment of the present invention Figure 1 ;

[0043] Fig.16 The effect of the AG anti-glare glass on the chamfer of the front hole of the crack under ultrasonic liquid in one embodiment of the present invention Figure 2 ;

[0044] Fig.17 This is a rendering of the chamfered edge of the AG anti-glare glass after it is cracked under ultrasonic liquid in one embodiment of the present invention;

[0045] Fig.18 This is a rendering of the chamfer of the rear hole of the AG anti-glare glass after it is split under ultrasonic liquid in one embodiment of the present invention;

[0046] Fig.19 This is a cross-sectional rendering of a finished AG anti-glare glass product in one embodiment of the present invention. DETAILED DESCRIPTION

[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0048] Please combine Figure 1-4 as well as Fig.11 The present invention discloses a processing method of AG anti-glare glass with high processing accuracy and efficiency, low product breakage rate and processing cost, and low requirements on operator skills. The processing method of AG anti-glare glass comprises the following steps:

[0049] S1. Sandblasting the incoming glass material so that a sand surface 110 is formed on the front side of the glass and a non-sand surface 120 is formed on the back side of the glass.

[0050] Specifically, the incoming glass is large-format unpolished glass. Before the incoming glass is transported to the sandblasting operation area of ​​the sandblasting machine, it is necessary to tear off the protective film on the surface of the glass to be sandblasted, while retaining the protective film (bottom film 130) on the part of the glass that does not need to be sandblasted. The glass is then loaded into a jig driven by a transmission mechanism, with the side of the glass with the protective film torn off facing upward (i.e., facing away from the jig), and the part of the glass where the protective film has not been torn off is in contact with the jig to prevent the glass surface from being scratched by the jig, thereby protecting the non-sand surface 120 of the glass.

[0051] Before sandblasting, the jig carrying the glass is moved in the working transport plane under the drive of the transmission mechanism, and the glass on the jig is sandblasted by a sandblaster suspended above the working transport plane of the glass material, so that the outlet surface of the sandblaster's spray gun spans the width of the glass to ensure that the sandblasting can cover the entire glass surface. At the same time, the working parameters of the sandblaster, such as sandblasting pressure, sandblasting distance, sandblasting angle, etc., are set to achieve the best sandblasting effect. In step S1, diamond sand is selected as the sandblasting sand, the sandblasting pressure of the glass material is 0.1-0.7MPa, and the sand particle size is 0.2-0.5mm to ensure that the sandblasting effect is uniform and will not excessively damage the glass surface; the sandblasting speed is 20-30m / s to maintain a stable sandblasting pressure and sandblasting efficiency; the sandblasting angle (the angle between the sandblasting gun and the glass surface) is 45°-90° to optimize the sandblasting effect and uniformity; the sandblasting distance is 10-30cm. Preferably, the sandblasting distance is 20 cm and the sandblasting angle is 90°. In other embodiments, the sandblasting parameters of the sandblasting machine can be adjusted according to product requirements and glass material and sand and water material.

[0052] When sandblasting, start the sandblasting machine so that the sandblasting water jet 200 of the spray gun performs high-speed sandblasting on the glass moving on the working transport plane. During the sandblasting process, it is necessary to ensure that most of the spray points fall on the glass surface that has not been sandblasted and moves below the spray gun nozzle, and the sandblasted glass continues to move in front of the spray point. In this way, the glass moves and the spray gun is fixed to achieve horizontal linear point-to-point striking, which improves the uniformity and efficiency of sandblasting. In this embodiment, after the glass is sandblasted, the roughness of the glass sand surface 110 is Ra 0.5-1.0μm to meet the subsequent processing requirements.

[0053] S2. Cut the sandblasted glass to form several glass sheets.

[0054] Specifically, step S2 includes:

[0055] S21, coating the sand surface 110 of the glass with protective oil 140 or covering it with a protective film. In step S21, the viscosity of the protective oil 140 is 20-50 cps to ensure that the protective oil 140 is rolled evenly and is easy to remove. In this embodiment, the protective oil 140 can be ink, and the protective oil 140 is coated on the sand surface 110 of the glass by rolling with a roller 300 or spraying with a spray gun, or the sand surface 110 of the glass is covered with a protective film to prevent the glass from being scratched during the subsequent handling or processing.

[0056] S22, cutting the glass into several glass pieces. In step S22, a cutter wheel or laser is used to cut the glass, so that the large-format glass 100 is sliced ​​into several small glass pieces, which is convenient for processing each small glass piece one by one to finally obtain a product of corresponding size. During the cutting process, it should be ensured that the cutting edge is smooth and has no obvious cracks. Then, the protective film on the non-sandy surface 120 of the glass is removed, and the non-sandy surface 120 of the glass piece is cleaned to remove dust or impurities on the non-sandy surface 120. In addition, in this scheme, the large-format glass 100 is sandblasted as a whole first, and then the sandblasted glass is cut into pieces, so that batch sandblasting of the glass pieces can be achieved to improve the sandblasting efficiency of the glass pieces.

[0057] S3. A laser beam 400 is emitted from the non-grinded surface 120 of the glass sheet, so that the interior of the glass sheet is laser engraved to form a chamfer pretreatment area, a hole pretreatment area and a hole chamfer pretreatment area. The chamfer pretreatment area, the hole pretreatment area and the hole chamfer pretreatment area are collectively referred to as a laser modified area 150.

[0058] After the front of the AG glass is sandblasted to form a sand surface 110, diffuse reflection will occur when the laser acts on the sand surface 110, causing the laser energy incident on the inside of the glass to attenuate, seriously affecting the glass processing quality. In this solution, the laser beam 400 is incident on the glass from the non-sand surface 120 of the glass, and laser pretreatment is performed to process the edges and holes of the glass, which can effectively solve the processing quality problem caused by diffuse reflection and prevent the edge of the product from breaking. Specifically, when the laser beam 400 is incident on the non-sand surface 120 of the glass sheet, firstly, due to the high smoothness of the non-sand surface 120, it helps the laser beam 400 to better focus on the cutting path, thereby improving the cutting accuracy; in the case of solving the diffuse reflection problem caused by the sand surface 110, the laser spot is small, the energy density is high, and it can be precisely focused, which can ensure the flatness of the cutting edge and the accuracy of the size. Secondly, during the laser cutting process, since the laser beam 400 moves relative to the material along a certain trajectory and forms a fixed-shaped slit, the smoothness of the non-sand surface 120 makes the heat generated during laser cutting more evenly distributed in the cutting area, which helps to reduce the heat-affected zone on the glass sheet and reduce the deformation of the workpiece, while maintaining the smoothness and aesthetics of the cutting surface and improving the cutting quality. Thirdly, compared with the sand surface 110, the scattering effect of the non-sand surface 120 is weaker, which can reduce the scattering loss of the laser during the incident process, so that more laser energy can be effectively used in the cutting process, improving the cutting efficiency and energy utilization. In addition, laser cutting has transmission characteristics. When the laser cutting machine is equipped with multiple CNC workbenches, CNC operation can be realized. For the non-sand surface 120 of the glass sheet, laser cutting can be more easily automated and intelligently controlled, reducing manual intervention and improving production efficiency and consistency. Figure 5 The figure shows the comparison of the effects of the laser beam incident on the glass sheet from the non-grinded surface and from the grinding surface. It can be seen that the laser cutting marks after the laser beam is incident from the non-grinded surface are obviously more regular and complete than the laser cutting marks after the laser beam is incident from the grinding surface. Figure 6 The figure shows the chamfering effect of a glass sheet when the laser beam is incident from the sanded surface and the non-sanded surface of the glass sheet. When the laser beam is incident from the sanded surface of the glass sheet, it will affect the real-time compensation function of the laser focus, resulting in the cutting chamfer not being in the center of the glass. Figure 6 It can be seen that when the laser beam is incident on the sand surface, the chamfer position is offset, which will cause product defects.

[0059] Please combine Figure 7In this solution, a laser engraving machine is used to perform laser engraving on a glass sheet. When a laser beam is used to perform laser engraving on a glass sheet, the laser beam emitted by the laser 101 of the laser engraving machine passes through a 1 / 2 wave plate 102, and the polarization state of the laser is changed by the 1 / 2 wave plate 102. The shape of the laser beam is further controlled by a beam control unit 103 to obtain a shaped beam to adapt to the shape that the part to be laser cut on the glass sheet needs to be formed in the end. After being reflected by the reflector 104, the shaped beam is incident on the glass sheet in the fixture loaded on the transmission mechanism 105 to perform laser engraving on the glass sheet. Among them, the beam control unit 103 can be one of a Bessel cutting head, a diffractive optical element DOE (diffractive optical element) lens, and a spatial light shaping device SLM (spatial light modulator), and is also equipped with a focusing objective lens to achieve processing of chamfers of different thicknesses. Through the Bessel cutting head, the diffraction optical element DOE lens or the spatial light shaping device SLM, the shape and energy distribution of the laser beam can be changed to achieve the shaping of the laser beam of the laser inner engraving machine. The shaped laser beam can accurately control the focal position and depth of the laser, which is suitable for complex internal engraving or fine surface processing. The beam control unit 103 shapes the laser beam into the desired chamfered shape beam or circular beam, and then focuses it into the inside of the transparent glass, and engraves the inside of the glass in a one-time multi-focus manner to form edge chamfers, holes and hole chamfers inside the glass. The chamfers and holes can be set arbitrarily and can be finely adjusted according to the final performance of the product. Laser focusing and engraving means that the shaped laser beam is focused into the inside of the transparent glass. Through precise focusing, the laser can perform one-time engraving in a multi-focus manner inside the glass, so that complex designs and patterns can be created inside without damaging the surface of the glass. Chamfers and holes are formed inside the glass sheet through laser engraving technology. The specific shapes of the chamfers and holes can be adjusted according to the final performance and requirements of the product. The shape and depth of the laser engraving can be flexibly set according to different application requirements to achieve the best visual effect and physical properties. Further preferably, in step S3, the laser beam power is 50-100W, the frequency is 50KHZ-250HZ, and the chamfering speed is 5-100mm / s to maintain stable chamfering quality and efficiency. In addition, during the laser pretreatment of the glass sheet, the sand surface of the glass sheet covered with protective oil or protective film needs to be placed face down on the jig to avoid scratching the glass sheet.

[0060] S4. Place the glass sheet in an etching solution for chemical etching.

[0061] In this scheme, before step S4, the protective oil or protective film on the surface of the glass sheet is removed so that the sand surface and the non-sand surface on the glass sheet are exposed, so that the glass sheet is fully in contact with the etching solution, and then the glass sheet is cleaned to remove the residual protective oil or attached dust impurities on the surface of the glass sheet. When etching the glass sheet, the glass sheet is completely immersed in the etching solution, and the sand surface, the edge after laser pretreatment and the hole are chemically etched simultaneously to improve the etching efficiency. By chemically etching the glass sheet, the thickness of the glass sheet can be thinned so that the chamfers, holes and the edges of the chamfers of the holes formed by laser engraving on the glass sheet can be exposed, which is conducive to the etching solution to penetrate into the gap of the above structure. The etching solution reacts with the glass sheet in the gap, so that the inside and outside of the glass are connected, so as to provide conditions for subsequent splitting operations and reduce the difficulty of splitting. Preferably, in step S4, the glass sheet is placed in a concentrated solution of NaOH or KOH with a mass fraction greater than 50% and a temperature higher than 120°C for chemical etching. Furthermore, when chemically etching the glass sheet, a bubbling device can be added to promote the circulation of high-temperature etching liquid. Figure 8 and Fig. 9 After the glass sheet is liquid polished (chemically etched), the excess material at the chamfers on the front and back of the glass sheet has been removed, leaving only the waste material at the product body connected to the product. Fig.10 The figure shows the effect comparison between the matte surface and non-matte surface of AG anti-glare glass after liquid polishing.

[0062] S5. Performing outer cracking on the glass sheet so that the edge of the glass sheet is chamfered.

[0063] In step S5, the glass sheet is cracked in shape by CO2 laser cracking, liquid nitrogen cracking or ice water quenching cracking. Specifically, when CO2 laser cracking is used, the CO2 laser beam is controlled to scan once along the existing cutting and modification track at the edge of the glass sheet, and the high energy of the laser is used to continuously perform high-temperature shocks on the surface of the object, so that stress cracks are generated on the surface of the object, and finally the purpose of cracking is achieved, so that the corners and waste of the glass sheet fall off automatically. The parameters of CO2 laser cracking are: power of 30W-200W, cracking speed of 20mm / s-200mm / s, and laser frequency of 500KHZ-5000KHZ. When using liquid nitrogen to crack, use a liquid nitrogen sprayer to spray the liquid nitrogen in the storage tank onto the surface of the glass sheet after liquid polishing. When the liquid nitrogen is sprayed onto the surface of the glass sheet, the glass sheet is suddenly cooled, causing the internal stress of the glass sheet to change. Since the chamfered edge of the glass sheet has been pre-processed by laser engraving, when the glass sheet cools down, stress cracks will be generated at this position, and the purpose of cracking will eventually be achieved, so that the corners of the glass sheet will automatically fall off. In addition, since the ambient temperature of chemical etching in this scheme is higher than 120°C, the glass sheet can be quickly pulled into ice water at the end of liquid polishing to quench the glass sheet. The cracks on the glass sheet quickly extend along the position of the laser engraving, achieving ice water quenching.

[0064] S6. Using ultrasonic underwater cracking to crack the glass sheet, so that holes are formed in the hole pretreatment area and the hole chamfer pretreatment area on the glass sheet.

[0065] Since the waste material in the center of the hole on the glass sheet is not removed after chemical etching, the waste material in the center of the hole needs to be further processed. Specifically, in this scheme, when ultrasonic underwater splitting is used to split the glass sheet, the ultrasonic generator transmits ultrasonic vibration energy to the glass sheet through a liquid medium. These vibration energies produce stress concentration inside the glass, which eventually causes the glass to break along a predetermined cutting line, so that the laser engraved part of the hole area on the glass sheet breaks, so as to remove the waste material in the center of the hole and achieve the purpose of hole splitting. By using ultrasonic underwater splitting to split the glass sheet, batch processing of the glass sheet can be achieved with high operating efficiency, and the liquid has a buffering effect, which can reduce scratches and edge collapse, and can improve production quality. In addition, the ultrasonic underwater splitting technology can ensure that the glass material is evenly stressed during the splitting process, reduce crack offset or irregular fracture caused by stress concentration, and thus improve the quality and efficiency of the splitting. Fig.12 The figure shows the effect comparison of AG anti-glare glass before and after hole cracking. It can be seen that after ultrasonic underwater cracking, the waste in the center of the hole on the glass sheet is evenly cut off, so that a smooth hole is formed on the glass sheet.

[0066] After liquid polishing, the silicate mixture in the strong alkaline solution will be embedded in the gaps formed by laser engraving on the glass sheet, so that white powder solids will adhere to the chamfers on the glass edges and holes after cracking. Cleaning is required to prevent affecting the subsequent process. The adhesion of white solid powder is as follows: Figure 13-16 As shown. To address this problem, in step S6, the glass sheet is placed in a citric acid solution with a concentration of 1%-30% or a NaOH solution with a concentration of 1%-20% for ultrasonic underwater cracking. In this solution, a citric acid solution or a NaOH solution is used as the liquid for ultrasonic underwater cracking. The citric acid solution or the NaOH solution can remove the silicate produced on the original laser engraved part of the glass sheet after chemical etching, so as to achieve the purpose of cleaning the glass while cracking the hole in the glass sheet, thereby improving the working efficiency. After the glass sheet is ultrasonically cracked in a citric acid solution or a NaOH solution, the effect is as follows: Figure 17-18 As shown, it can be seen that the cleanliness of the glass sheet is relatively high. After the glass sheet hole is cracked, the glass sheet is cleaned again to remove the chemical agent residue on the surface of the glass sheet. Fig.19 The cross-sectional effect diagram of the finished AG anti-glare glass is shown. It can be seen that the non-grit surface of the glass sheet is highly smooth and its chamfer is flat and uniform.

[0067] When the above-mentioned ultrasonic underwater splitting method is used to split the glass sheet, firstly, during the ultrasonic splitting process, an isolation film is adhered to the surface of the material, which separates the material from the liquid to prevent the flow of the liquid from causing the material to shift. At the same time, since the isolation film has adhesion, the positions of multiple independent parts are fixed under the bonding action of the isolation film, which helps to improve the positioning accuracy of the material. Secondly, the ultrasonic generator transmits ultrasonic waves to the material with the help of liquid and splits it. Due to the mechanical action of ultrasonic waves, the splitting process can be ensured to be more uniform and controllable, thereby improving the quality of the splitting. Thirdly, the ultrasonic underwater splitting technology is suitable for various types of glass materials, is not limited by material thickness, shape, etc., and has strong adaptability and flexibility. In addition, the ultrasonic underwater splitting technology can be mass-produced, reduce manual intervention, and improve production efficiency.

[0068] The processing method of the AG anti-glare glass of the present invention has at least the following beneficial effects:

[0069] 1) Pre-process the glass sheet with laser engraving. By shaping the laser beam, the position of the laser engraving can be accurately controlled to achieve efficient and precise processing of AG glass, thereby improving processing accuracy and yield rate;

[0070] 2) The laser beam is incident from the non-grit surface of the glass sheet, which reduces the damage area of ​​AG glass, reduces cracks and edge collapse during processing, and reduces the breakage rate;

[0071] 3) Combine sandblasting of large pieces of glass with laser processing to batch etch and crack glass sheets, thus achieving fast and efficient processing of AG glass and improving production efficiency;

[0072] 4) By optimizing the processing flow, waste and loss in the processing process are reduced, and the processing cost is reduced. It has low skill requirements for operators and reduces the difficulty of product processing.

[0073] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0074] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for processing AG anti-glare glass, characterized in that: The following steps are involved: S1. Sandblasting the incoming glass material so that the front side of the glass forms a sand surface and the back side of the glass forms a non-sand surface; S2, cutting the sandblasted glass to form a number of glass sheets; S3, irradiating a laser beam from the non-grinded surface of the glass sheet, so that the inside of the glass sheet is laser engraved to form a chamfer pre-processing area, a hole pre-processing area and a hole chamfer pre-processing area; S4, placing the glass sheet into an etching solution for chemical etching; S5, performing external cracking on the glass sheet so that the edge of the glass sheet is chamfered; S6. Using ultrasonic underwater cracking to crack the glass sheet, so that holes are formed in the hole pretreatment area and the hole chamfer pretreatment area on the glass sheet.

2. The method for processing AG anti-glare glass according to claim 1, characterized in that: In step S1, the sandblasting pressure of the glass material is 0.1-0.7 MPa, the sand particle size is 0.2-0.5 mm, the sandblasting speed is 20-30 m / s, the sandblasting angle is 45°-90°, the sandblasting distance is 10-30 cm, and the roughness of the glass sand surface is Ra0.5-1.0 μm.

3. The method for processing AG anti-glare glass according to claim 1, characterized in that: Step S2 includes: S21. Apply protective oil or cover the sand surface of the glass with a protective film; S22, cutting the glass into a plurality of glass sheets.

4. The method for processing AG anti-glare glass according to claim 3, characterized in that: In step S21, the viscosity of the protective oil is 20-50 cps.

5. The method for processing AG anti-glare glass according to claim 3, characterized in that: In step S22, the glass is cut by a cutter wheel or laser.

6. The method for processing AG anti-glare glass according to claim 1, characterized in that: In step S3, the laser beam power is 50-100 W, the frequency is 50 KHZ-250 Hz, and the chamfering speed is 5-100 mm / s.

7. The method for processing AG anti-glare glass according to claim 3, characterized in that: Before step S4, the protective oil or protective film on the surface of the glass sheet is removed.

8. The method for processing AG anti-glare glass according to claim 1, characterized in that: In step S4, the glass sheet is placed in a concentrated solution of NaOH or KOH with a mass fraction greater than 50% and a temperature greater than 120° C. for chemical etching.

9. The method for processing AG anti-glare glass according to claim 8, characterized in that: In step S5, the glass sheet is externally cracked by CO2 laser cracking, liquid nitrogen cracking or ice water quenching cracking.

10. The method for processing AG anti-glare glass according to claim 1, characterized in that: In step S6, the glass sheet is placed in a citric acid solution with a concentration of 1% to 30% or a NaOH solution with a concentration of 1% to 20% for ultrasonic underwater cracking.

Citation Information

Patent Citations

  • Glass with matte paper effect and preparation method thereof

    CN113716875A

  • Single-side thinning method of bonding wafer

    CN117219502A

  • Integrated thinning and chamfering processing method for ultra-thin glass

    CN118930062A

  • Method of manufacturing chemically strengthened glass plate

    US20130219966A1

Cited By

  • Laser chamfering and Bessel cutting auxiliary line combined disc cutting process

    CN121310865A